Use of the rotating wall vessel technology to study the effect of shear stress on growth behaviour of Pseudomonas aeruginosa PA01 - Aurélie Crabbé; Patrick De Boever; Rob Van Houdt; Hugo Moors; Max Mergeay; Pierre Cornelis (Environmental Microbiology, 2008)
Summary The biofilm phenotype of Pseudomonas aeruginosa enables this opportunistic pathogen to develop resistance to the immune system and antimicrobial agents. Pseudomonas aeruginosa biofilms are generated under varying levels of shear stress, depending on the infection site. In the lung mucus of cystic fibrosis (CF) patients, P. aeruginosa forms matrix‐enclosed microcolonies which cause chronic infections representing the major cause of mortality in CF patients. The lung mucus of CF patients is probably characterized by low fluid shear as the main shear‐causing factor, i.e. mucociliary clearance, is absent. In this study, the influence of fluid shear on the growth behaviour of P. aeruginosa PA01 was investigated using a low‐shear suspension culture device, the rotating wall vessel (RWV). Cultivation in low shear induced a self‐aggregating phenotype of P. aeruginosa PA01, resulting in the formation of biofilms in suspension similar to what has been described in CF mucus. The addition of a ceramic bead to the culture medium in the RWV created a higher‐shear condition which led to the formation of surface‐attached rather than suspension biofilms. In low‐shear culture conditions, a significant increase of the rhl N ‐butanoyl‐ l ‐homoserine lactone (C 4 ‐HSL) directed quorum sensing (QS) system, and the psl polysaccharide synthetic locus was demonstrated using gene expression analysis. Accordingly, the low‐shear condition induced a higher production of rhamnolipids, which is controlled by the C 4 ‐HSL QS‐system and is known to play a role in CF lung pathology. These results indicate that fluid shear has an impact on the growth phenotype of P. aeruginosa which might play a role in CF lung infections caused by this bacterium.